SEBARAN STATUS BAHAN ORGANIK SEBAGAI DASAR PENGELOLAAN KESUBURAN TANAH PADA BEBERAPA PENGGUNAAN LAHAN DI DESA BAKUBAKULU KECAMATANPALOLO KABUPATEN SIGI - Amelia, Rezi; Darman, Saiful; M, Misriana (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study aimed to determine the distribution of organic matter status as a basis for soil fertility management across different land uses in Bakubakulu Village, Palolo Subdistrict, Sigi District. Soil analysis was conducted at the Soil Science Laboratory Unit, Faculty of Agriculture, Tadulako University, from July to August 2022. Soil samples were collected from various land use types, including primary dry land forest, secondary dry land forest, mixed dry land agriculture, and bushes. A total of 16 soil samples were taken and composited into eight samples. The analysis revealed that land unit (LU) 2.2 had the highest organic matter status (3.75%) and C-Organic content (2.18%), meeting moderate criteria. The results also showed that soil pH was highest in LU 1.2 (6.67), while N-total was highest in LU 3.2 (0.31%). Soil texture varied across the samples, with different land use types exhibiting distinct textures, ranging from sandy loam to loamy sand. The findings of this study provide valuable insights for optimizing soil fertility management strategies across different land uses in the region.